Socioeconomic and racial/ethnic disparities in receipt of palliative care among patients with metastatic hepatocellular carcinoma. Issue 8 (10th September 2021) - Alterio, Rodrigo E.; Ju, Michelle R.; Wang, Sam C.; Mansour, John C.; Yopp, Adam; Porembka, Matthew R.
Abstract: Background: Patients with metastatic hepatocellular carcinoma (HCC) suffer symptoms of both end‐stage liver disease and cancer. Palliative care (PC) enhances the quality of life via symptom control and even improves survival for some cancers. Our study characterized rates of PC utilization among metastatic HCC patients and determined factors associated with PC receipt. Methods: We conducted a retrospective review of adult National Cancer Database patients diagnosed with metastatic HCC between 2004 and 2016. Chi‐square tests were used to analyze two cohorts: those who received PC and those who did not. Logistic regression was performed to assess the impact of clinicodemographic factors on the likelihood of receiving PC. Results: PC utilization was low at just 17%. Later year of diagnosis, insured status, and higher education level were associated with an increased likelihood of receiving PC. Treatment at academic centers or integrated network cancer programs increased the likelihood of receiving PC compared to treatment at a community center (odds ratio [OR] = 1.17, 95% confidence interval [CI] = 1.03–1.33 and OR = 1.25, 95% CI = 1.07–1.45; respectively). Hispanics were significantly less likely to received PC than non‐Hispanic Whites (OR = 0.73, 95% CI = 0.64–0.82). Conclusions: PC utilization among patients with metastatic HCC remains low. Targeted efforts should be enacted to increase the delivery of PC in this group.